Roya Partial Jaminan Hak Atas Tanah dalam Perjanjian Kredit di Bank Berdasarkan Undang-Undang Nomor 4 Tahun 1996 - Lendrawati Lendrawati; Hirit Hastari (Fakultas Hukum, Universitas Internasional Batam, 2018)
Responsibility Rights Law is the unification in the collateral institutes in Indonesia. The establishment of this responsibility rights obliged to be registered as well as the dilation of of Responsiblity Rights. Responsibility Rights dilation is folowed by the enforcement of writng off the Responsibility Rights that can be done with dilation and Partial Dilation as prepared in in Article 2 of Undang-Undang Hak Tanggungan (Law of Responsibility Rights). But the validity of Regulation of State Minister of Agriculture Number 3 Year of 1997 is very contrary to the Dilation and Partial Dilation Stipulation as provided in Article 2 Law of Responsibility Rights. Of course this situation causes some problems, because there are difference arrangements in conducting dilation upon Responsibility Rights encumbering. In this research it will be discussed the enforcement of partial Dilation of Responsibility Rights in the practice that occurs in Batam after the validity of Regulation of State Minister of Agriculture/ Head of National Land Form Number 3 year of 1997 and the constraints faced by Landform Office in Batam in the enforcement of Partial Dilation of Responsibility Rights after the validity of Regulation of State Minister of Agriculture Head of Natiaonal Landform Number 3 Year of 1997. The Research Method applied in discussing the topic of this skripsi is the juridical - empirical approach through the collection of primary and secondary data. Research is done on parties involved in the Roya Partial process, i.e. the Notary/ Land Deed Official (PPAT), Banking Institution, and the Land Office of Batam City.